A lithium ion hybrid supercapacitor with matched positive and negative electrodes and a method for preparing the same

By using carbon aerogel-Liferomanganese and Ferrophosphate composite positive electrode material and phosphorus carbon composite negative electrode material, the problem of poor matching of positive and negative electrode of lithium-ion hybrid supercapacitor is solved, and electrochemical performance with high energy density, high power density and excellent cycle stability is achieved.

CN117936277BActive Publication Date: 2025-03-11WUHAN INSTITUTES OF ADVANCED TECHNOLOGY CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410004892.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-03
Publication Date
2025-03-11
Estimated Expiration
2044-01-03

AI Technical Summary

Technical Problem

The positive and negative electrodes of existing lithium-ion hybrid supercapacitors have poor matching in terms of kinetics and specific capacity, resulting in low energy density, low power density and poor long cycle stability.

Method used

The positive electrode material is prepared by the new sol gel-one-step carbonization method, and the negative electrode material is prepared by rotary evaporation method to achieve the kinetics and specific capacity matching of the positive and negative electrodes.

Benefits of technology

The energy density, power density and cycling stability of lithium-ion hybrid supercapacitors are improved, and the maximum matching of positive and negative electrodes is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004646472320000131
    Figure BDA0004646472320000131
  • Figure BDA0004646472320000141
    Figure BDA0004646472320000141
Patent Text Reader

Abstract

The present invention belongs to the field of electrochemical energy storage technology, and specifically relates to a lithium ion hybrid supercapacitor with matched positive and negative electrodes and a preparation method thereof. The lithium ion hybrid supercapacitor prepared in the present invention uses a high-capacity capacitor-battery hybrid positive electrode material (carbon aerogel-manganese iron phosphate lithium composite positive electrode material) and a high-rate, long-cycle-life battery-type negative electrode material (phosphorus-carbon composite negative electrode material) as the positive and negative electrode materials of the lithium ion hybrid supercapacitor, which is conducive to achieving the maximum degree of positive and negative electrode matching. The lithium ion hybrid supercapacitor assembled therefrom has both high energy density, high power density and excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical energy storage, and in particular relates to a lithium ion hybrid supercapacitor with matched positive and negative electrodes and a preparation method thereof. Background Art

[0002] As a new type of energy storage device, lithium-ion hybrid supercapacitors combine the advantages of lithium-ion batteries and supercapacitors, with high energy density, high power density and long cycle life. They are considered to be one of the most promising electrochemical energy storage devices.

[0003] Lithium-ion hybrid supercapacitors are usually assembled with battery-type negative electrode materials and capacitor-type positive electrode materials, and their electrochemical performance is greatly affected by the matching of positive and negative electrode materials. Lithium-ion battery positive electrode materials such as lithium iron phosphate and lithium iron manganese phosphate cannot generally be directly used as positive electrode materials for lithium-ion hybrid supercapacitors. Existing positive electrode materials for lithium-ion hybrid supercapacitors often use carbon-based materials with high specific surface areas, such as activated carbon, template carbon, porous graphene, carbon aerogel and other materials, but compared with high specific capacity negative electrode materials with chemical embedding / desorption mechanisms, the charge storage of these positive electrode materials is based on physical adsorption / desorption processes, and the discharge capacity is low, thereby limiting the energy density of the capacitor; the negative electrode of existing lithium-ion hybrid supercapacitors often uses battery-type materials such as graphite, soft carbon and hard carbon, but the rate performance of these carbon-based negative electrode materials is usually poor, and the lithium ion embedding / desorption rate on the negative electrode is much lower than the physical charge adsorption / desorption rate on the positive electrode, which often causes kinetic mismatch and cycle attenuation between the positive and negative electrodes, limiting the overall performance of lithium-ion hybrid supercapacitors. From the above, we can see that the mismatch between the low kinetics of the embedded negative electrode and the fast kinetics of the capacitive positive electrode, as well as the difficulty in balancing the high specific capacity of the chemically embedded negative electrode and the low specific capacity of the physically adsorbed positive electrode, will lead to low energy density, low power density and poor long-cycle stability of lithium-ion hybrid supercapacitors, which seriously hinder the development of lithium-ion hybrid supercapacitors.

[0004] The matching of the reaction speed of positive and negative electrodes has an important influence on the performance of lithium-ion hybrid supercapacitors. Therefore, the development of lithium-ion hybrid supercapacitor negative electrode materials with fast charging capability has become a research focus. As a new type of alloy negative electrode material, black phosphorus has the potential to be used as a high specific energy and high rate negative electrode material, such as CN112018363A, because of its ultra-high theoretical specific capacity (2596mAh / g), high electronic conductivity (300S / m), ultra-low lithium ion diffusion barrier (0.08eV) and relatively high lithium deintercalation potential platform (0.7V). However, phosphorus has low conductivity, and its volume expansion rate is greater than 300% during the charging and discharging process. The structure is very unstable after nano-sizing, which leads to poor long-cycle stability of phosphorus negative electrode materials. How to better improve the volume expansion problem of black phosphorus during the charging and discharging process, and better apply it as the negative electrode of lithium-ion hybrid supercapacitors to achieve a better match with the positive electrode of lithium-ion hybrid supercapacitors is still a technical problem. Summary of the invention

[0005] In order to solve the problems of low energy density, low power density and poor long-cycle stability caused by poor matching of positive and negative electrodes in kinetics and specific capacity of existing lithium-ion hybrid supercapacitors, the present invention provides a lithium-ion hybrid supercapacitor with matched positive and negative electrodes and a preparation method thereof, by preparing and using a carbon aerogel-lithium iron manganese phosphate composite positive electrode material with high capacity and a phosphorus-carbon composite negative electrode material with high rate and long-cycle stability, so that the positive and negative electrodes have a high matching in terms of kinetic process and specific capacity balance, and the lithium-ion hybrid supercapacitor finally prepared exhibits excellent electrochemical performance. The specific technical scheme of the present invention is:

[0006] In a first aspect, a method for preparing a lithium-ion hybrid supercapacitor with matched positive and negative electrodes is provided, comprising the following steps:

[0007] Step 1: taking a carbon aerogel-lithium manganese iron phosphate composite positive electrode material, a conductive agent, a binder and a solvent, stirring and dissolving them to obtain a positive electrode slurry, and then coating it on a current collector sheet to obtain a positive electrode sheet;

[0008] Step 2: taking a phosphorus-carbon composite negative electrode material, a conductive agent, a binder and a solvent, stirring and dissolving them to obtain a negative electrode slurry, and then coating the slurry on a current collector to obtain a negative electrode sheet;

[0009] Step 3: pre-lithiate the negative electrode sheet, and then assemble the negative electrode sheet, the positive electrode sheet and the electrolyte to obtain the capacitor.

[0010] Specifically, the method for preparing the carbon aerogel-lithium manganese iron phosphate composite positive electrode material in step 1 includes:

[0011] Step (1), mixing an iron source, a manganese source, a lithium source, a phosphorus source and deionized water to prepare a solution A, uniformly mixing resorcinol, formaldehyde, sodium carbonate and deionized water to form a solution B, slowly adding solution A to solution B with stirring to form a solution C, and allowing solution C to stand at room temperature to form a sol;

[0012] Step (2), heating the sol to gel and age to obtain a hydrogel, and performing solvent replacement and supercritical drying on the hydrogel to obtain an organic aerogel-lithium manganese iron phosphate precursor mixture;

[0013] Step (3), carbonizing the organic aerogel-lithium iron manganese phosphate precursor mixture under an inert atmosphere to obtain a carbon aerogel-lithium iron manganese phosphate composite positive electrode material.

[0014] The above-mentioned positive electrode material preparation process adopts a new sol-gel-one-step carbonization method. Compared with the conventional two-step carbonization preparation process (in situ growth of lithium manganese iron phosphate in the carbon aerogel skeleton), this method is simpler and more efficient, and can significantly reduce energy consumption and cost.

[0015] More specifically, the resting time in step (1) is 20 to 30 hours;

[0016] More specifically, the iron source in step (1) is a soluble iron source selected from one of ferrous sulfate, ferrous oxalate, ferrous acetate or ferrous nitrate.

[0017] More specifically, the manganese source in step (1) is a soluble manganese source selected from one of manganese sulfate, manganese nitrate, manganese acetate and manganese chloride.

[0018] More specifically, the phosphorus source in step (1) is selected from one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and ammonium phosphate.

[0019] More specifically, the molar ratio of the iron source, manganese source, lithium source and phosphorus source in solution A in step (1) is 0.1-0.6:0.4-0.9:1:1-1.05, calculated as Fe, Mn, Li and PO4 respectively.

[0020] More specifically, the solid content of the solution A in step (1) is 40-60%.

[0021] More specifically, the lithium source in step (1) is one of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate and lithium nitrate.

[0022] More specifically, in the solution B in step (1), the molar ratio of resorcinol to formaldehyde is 1:2, the molar ratio of resorcinol to sodium carbonate is 100-1500:1, and the molar ratio of deionized water to resorcinol is 4-90.

[0023] More specifically, in step (1), the molar ratio of the Li element in the solution A to the resorcinol in the solution B is 1:1-4.

[0024] More specifically, the heating temperature in step (2) is 40 to 60° C., and the heating time is 16 to 24 hours.

[0025] More specifically, the aging temperature in step (2) is 60 to 80° C., and the aging time is 16 to 24 hours.

[0026] More specifically, the solvent replacement reagent in step (2) is ethanol, the solvent replacement time is 4 to 6 days, and the ethanol is replaced every 8 hours.

[0027] More specifically, the operation process of supercritical drying in step (2) is to put the hydrogel after solvent replacement into an autoclave, seal it, heat it to a set temperature of 50-60°C at a heating rate of 1°C / min, set the pressure to 14-20MPa, keep it warm for 2h, and then slowly release the supercritical fluid;

[0028] More specifically, the temperature of the carbonization treatment in step (3) is 600-900° C., the time is 1.5-3 h, and the heating rate is 2-5° C. / min.

[0029] Specifically, the method for preparing the phosphorus-carbon composite negative electrode material in step 2 includes:

[0030] S1, dispersing and dissolving the polymer and the conductive agent in a solvent to obtain a polymer solution;

[0031] S2, mixing black phosphorus, graphite, carbon nanotubes and a small molecule modifier and then ball milling to obtain an interface-modified phosphorus-carbon composite material;

[0032] S3, dispersing the interface-modified phosphorus-carbon composite material in a polymer solution to obtain a homogeneous dispersion;

[0033] S4. Rotary evaporate the homogeneous dispersion to obtain a phosphorus-carbon composite negative electrode material coated with a conductive polymer film.

[0034] More specifically, the polymer in step S1 is selected from any one of polyacrylic acid, polyimide, polyaniline, polypyrrole, polythiophene, and polyacetylene, and the conductive agent is selected from any one of graphene, carbon black, carbon nanotubes, and fullerene.

[0035] More specifically, the solvent in step S1 is water or an organic solvent, and the organic solvent is selected from any one of N-methylpyrrolidone, ethanol, acetone, N,N-dimethylformamide, and acetonitrile.

[0036] More specifically, the mass fraction of the polymer solution in step S1 is 1-20%, and the mass ratio of the polymer to the conductive agent in the polymer solution is 2:1 to 16:1.

[0037] More specifically, the concentration of the interface-modified phosphorus-carbon composite material in the homogeneous dispersion in step S3 is 0.1-100 g / L.

[0038] More specifically, the heating temperature of the rotary evaporation in step S4 is 50-300° C., the rotation speed is 10-280 rpm, and the pressure is 50-80 kPa.

[0039] More specifically, the small molecule modifier in step S2 is any one of urea, melamine, polydimethyldiallylammonium chloride, and p-phenylenediamine.

[0040] More specifically, in the interface-modified phosphorus-carbon composite material in step S2, the mass proportions of black phosphorus, graphite, carbon nanotubes and small molecule modifiers are 50-85%, 10-40%, 1-20% and 1-3%, respectively.

[0041] Specifically, the conductive agent in step 1 and step 2 is selected from at least one of conductive carbon black, carbon nanotubes or graphene.

[0042] Specifically, the binders in step 1 and step 2 are both selected from at least one of polyvinylidene fluoride and polytetrafluoroethylene.

[0043] Specifically, the solvents in step 1 and step 2 are both N-methylpyrrolidone.

[0044] Specifically, in step 1, the mass ratio of the carbon aerogel-lithium manganese iron phosphate composite positive electrode material, the conductive agent and the binder is 7-8:1:1-2, and the solid content of the positive electrode slurry is 40-60wt%.

[0045] Specifically, the current collector sheets in step 1 and step 2 are selected from at least one of copper foil, titanium foil, stainless steel foil, copper mesh, titanium mesh, stainless steel mesh or nickel mesh.

[0046] Specifically, in step 2, the mass ratio of the phosphorus-carbon composite negative electrode material, the conductive agent and the binder is 7-8:1:1-2, and the solid content of the negative electrode slurry is 40-60wt%.

[0047] Specifically, the pre-lithiation in step 3 is to directly contact the metal lithium foil with the negative electrode sheet for 0.5 to 2 hours in the presence of an electrolyte.

[0048] More specifically, the black phosphorus in step S2 is at least one of black phosphorus nanosheets and black phosphorus quantum dots.

[0049] Specifically, the electrolyte in step 3 is 1M LiPF6 dissolved in EC / DEC (volume ratio 1:1) solution.

[0050] In a second aspect, the present invention provides a lithium ion hybrid supercapacitor prepared by the above method.

[0051] The beneficial effects brought by the present invention are as follows:

[0052] (1) The present invention adopts a novel sol-gel-one-step carbonization method to prepare a carbon aerogel-lithium manganese iron phosphate composite positive electrode material, which has the advantages of being simple and efficient, reducing energy consumption and low cost, and being easy to realize industrial large-scale production;

[0053] (2) In the carbon aerogel-lithium iron manganese phosphate composite positive electrode material provided by the method of the present invention, lithium iron manganese phosphate nanoparticles are uniformly filled in the pores of the carbon aerogel, iron and manganese are evenly distributed, and the three-dimensional conductive network constructed by the carbon aerogel continuously and evenly coats and penetrates the lithium iron manganese phosphate particles, which can effectively improve the conductive properties of lithium iron manganese phosphate and facilitate the rapid transmission of ions in the electrolyte;

[0054] (3) The phosphorus-carbon composite negative electrode material prepared by the method of the present invention comprises dispersing a polymer and a conductive agent in an organic solvent, then adding the phosphorus-carbon composite material to prepare a homogeneous dispersion, and finally drying by rotary evaporation, so that the polymer has sufficient time to arrange and self-assemble its molecular chains, and the small molecule modifier adheres the polymer to the phosphorus-carbon surface through chemical bonding, thereby achieving the purpose of uniformly coating the phosphorus-carbon negative electrode material, making the conductivity of the coated film composed of the polymer uniform, controllable, and uniformly coated, with good conductivity and good inhibition of the volume expansion of black phosphorus during the charge and discharge process, showing excellent rate performance and long cycle stability;

[0055] (4) The lithium-ion hybrid supercapacitor prepared in the present invention uses a high-capacity capacitor-battery hybrid positive electrode material (carbon aerogel-lithium iron manganese phosphate composite positive electrode material) and a high-rate, long-cycle-life battery-type negative electrode material (phosphorus-carbon composite negative electrode material) as the positive and negative electrode materials of the lithium-ion hybrid supercapacitor, which is conducive to achieving maximum positive and negative electrode matching. The lithium-ion hybrid supercapacitor assembled therefrom has high energy density, high power density and excellent cycle stability. DETAILED DESCRIPTION

[0056] The technical solution of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

[0057] Example 1

[0058] 1. Preparation of phosphorus-carbon composite negative electrode materials:

[0059] S1. Disperse and dissolve 2 g of polyacrylic acid and 1 g of graphene in 27 g of N-methylpyrrolidone, and stir magnetically for 12 h to obtain a polymer solution with a mass fraction of 10%;

[0060] S2, mixing black phosphorus nanosheets, graphite, carbon nanotubes and urea and then ball milling to obtain an interface-modified phosphorus-carbon composite material, wherein the phosphorus-carbon composite material contains 74wt% of black phosphorus, 20wt% of graphite, 5wt% of carbon nanotubes and 1wt% of urea;

[0061] S3, taking 5g of the interface-modified phosphorus-carbon composite material and dispersing it in the polymer solution, ultrasonicating it for 5min, and magnetically stirring it for 6h to achieve uniform dispersion, and obtaining a 50g / L homogeneous dispersion;

[0062] S4. Pour the homogeneous dispersion into a 300 ml rotating bottle, adjust the temperature of the heating oil bath to 230°C, adjust the rotation speed to 50 rpm, start the vacuum pump, adjust the pressure in the rotating bottle to 75 kPa, and introduce cooling water. After 30 minutes, a phosphorus-carbon composite negative electrode material coated with a conductive polymer film is obtained.

[0063] 2. Preparation of carbon aerogel-lithium manganese iron phosphate composite positive electrode material:

[0064] (1) 0.02 mol of ferrous nitrate, 0.03 mol of manganese nitrate, 0.025 mol of lithium carbonate, 0.05 mol of ammonium dihydrogen phosphate and deionized water are mixed to prepare solution A, so that the solid content is 40%; 0.2 mol of resorcinol (R), 0.4 mol of formaldehyde (F), 2 mmol of sodium carbonate (C) and 18 mol of deionized water (W) are uniformly mixed to form solution B; solution A is slowly added to solution B, stirred at room temperature for 4 hours to form solution C, and solution C is slowly injected into a cylindrical mold and allowed to stand at room temperature for 24 hours to form a sol;

[0065] (2) heating the sol at 50°C in a water bath for 24 hours, and then heating the sol to 75°C for further aging for 24 hours after the sol gels to obtain a dark red hydrogel; soaking the hydrogel sample in an ethanol solvent for 5 days, replacing the ethanol every 8 hours; placing the hydrogel after solvent replacement in an autoclave, sealing it, and heating it to a set temperature of 50°C at a heating rate of 1°C / min, with a set pressure of 15MPa. After keeping the temperature for 2 hours, slowly releasing the supercritical fluid to obtain an organic aerogel-lithium manganese iron phosphate precursor mixture;

[0066] (3) The organic aerogel-lithium iron manganese phosphate precursor mixture is carbonized in an argon atmosphere, heated to 600°C at a rate of 2°C / min, kept at this temperature for 2 hours, and then cooled in the furnace to obtain a carbon aerogel-lithium iron manganese phosphate composite positive electrode material.

[0067] 3. Preparation of lithium-ion hybrid supercapacitors with matched positive and negative electrodes

[0068] Step 1, taking 8g of the above-mentioned carbon aerogel-lithium manganese iron phosphate composite positive electrode material, 1g of carbon black, 1g of polyvinylidene fluoride and N-methylpyrrolidone, stirring and dissolving them to obtain a positive electrode slurry (solid content 40wt%), and then coating it on a copper foil to obtain a positive electrode sheet;

[0069] Step 2, taking 8g of phosphorus-carbon composite negative electrode material, 1g of carbon black, 1g of polyvinylidene fluoride and N-methylpyrrolidone, stirring and dissolving them to obtain a negative electrode slurry (solid content 50%), and then coating it on a copper foil sheet to obtain a negative electrode sheet;

[0070] Step 3: In the presence of an electrolyte, the metal lithium foil is directly contacted with the negative electrode for 1 hour, and then the negative electrode, the positive electrode and the electrolyte are assembled to obtain the lithium-ion hybrid supercapacitor; the electrolyte is 1M LiPF6 dissolved in EC / DEC (volume ratio 1:1) solution.

[0071] Example 2

[0072] 1. Preparation of phosphorus-carbon composite negative electrode materials:

[0073] S1, dispersing and dissolving 9 g of polyimide and 1 g of carbon black in 90 g of N-methylpyrrolidone, stirring magnetically for 12 h, to obtain a polymer solution with a mass fraction of 1%;

[0074] S2, mixing black phosphorus nanosheets, graphite, carbon nanotubes and p-phenylenediamine and then ball milling to obtain an interface-modified phosphorus-carbon composite material, wherein the phosphorus-carbon composite material contains 85wt% of black phosphorus, 10wt% of graphite, 2wt% of carbon nanotubes and 3wt% of urea;

[0075] S3, taking 5g of the interface-modified phosphorus-carbon composite material and dispersing it in the polymer solution, ultrasonicating it for 5min, and magnetically stirring it for 6h to achieve uniform dispersion, and obtaining a 0.1g / L homogeneous dispersion;

[0076] S4. Pour the homogeneous dispersion into a 300 ml rotating bottle, adjust the temperature of the heating oil bath to 300°C, adjust the rotation speed to 150 rpm, start the vacuum pump, adjust the pressure in the rotating bottle to 55 kPa, and introduce cooling water. After 30 minutes, a phosphorus-carbon composite negative electrode material coated with a conductive polymer film is obtained.

[0077] 2. Preparation of carbon aerogel-lithium manganese iron phosphate composite positive electrode material:

[0078] (1) 0.026 mol of ferrous nitrate, 0.04 mol of manganese nitrate, 0.033 mol of lithium carbonate, 0.066 mol of ammonium dihydrogen phosphate and deionized water are mixed to prepare solution A, so that the solid content is 40%; 0.2 mol of resorcinol (R), 0.4 mol of formaldehyde (F), 2 mmol of sodium carbonate (C) and 18 mol of deionized water (W) are uniformly mixed to form solution B; solution A is slowly added to solution B, stirred at room temperature for 4 hours to form solution C, and solution C is slowly injected into a cylindrical mold and allowed to stand at room temperature for 24 hours to form a sol;

[0079] (2) heating the sol at 50°C in a water bath for 24 hours, and then heating the sol to 75°C for further aging for 24 hours after the sol gels to obtain a dark red hydrogel; soaking the hydrogel sample in an ethanol solvent for 5 days, replacing the ethanol every 8 hours; placing the hydrogel after solvent replacement in an autoclave, sealing it, and heating it to a set temperature of 50°C at a heating rate of 1°C / min, with a set pressure of 15MPa. After keeping the temperature for 2 hours, slowly releasing the supercritical fluid to obtain an organic aerogel-lithium manganese iron phosphate precursor mixture;

[0080] (3) The organic aerogel-lithium iron manganese phosphate precursor mixture is carbonized in an argon atmosphere, heated to 700°C at a rate of 2°C / min, kept at this temperature for 2 hours, and then cooled in the furnace to obtain a carbon aerogel-lithium iron manganese phosphate composite positive electrode material.

[0081] 3. Preparation of lithium-ion hybrid supercapacitors with matched positive and negative electrodes

[0082] Step 1, taking 7g of the above-mentioned carbon aerogel-lithium manganese iron phosphate composite positive electrode material, 1g of carbon black, 2g of polyvinylidene fluoride and N-methylpyrrolidone, stirring and dissolving them to obtain a positive electrode slurry (solid content 50%), and then coating it on a copper foil to obtain a positive electrode sheet;

[0083] Step 2, taking 7g of phosphorus-carbon composite negative electrode material, 1g of carbon black, 1g of polyvinylidene fluoride and 1g of N-methylpyrrolidone, stirring and dissolving them to obtain a negative electrode slurry (solid content 60%), and then coating it on a copper foil sheet to obtain a negative electrode sheet;

[0084] Step 3: In the presence of an electrolyte, the metal lithium foil is directly contacted with the negative electrode for 2 hours, and then the negative electrode, the positive electrode and the electrolyte are assembled to obtain the lithium-ion hybrid supercapacitor; the electrolyte is 1M LiPF6 dissolved in EC / DEC (volume ratio 1:1) solution.

[0085] Example 3

[0086] 1. Preparation of phosphorus-carbon composite negative electrode materials:

[0087] S1, dispersing and dissolving 9 g of polyaniline and 1 g of carbon nanotubes in 90 g of N-methylpyrrolidone, and magnetically stirring for 12 h to obtain a polymer solution with a mass fraction of 10%;

[0088] S2, mixing black phosphorus quantum dots, graphite, carbon nanotubes and polydimethyldiallylammonium chloride and then ball milling to obtain an interface-modified phosphorus-carbon composite material, wherein the phosphorus-carbon composite material contains 60wt% of black phosphorus, 20wt% of graphite, 9wt% of carbon nanotubes and 1wt% of urea;

[0089] S3, taking 10g of the interface-modified phosphorus-carbon composite material and dispersing it in the polymer solution, ultrasonicating it for 5min, and magnetically stirring it for 6h to achieve uniform dispersion, and obtaining a 100g / L homogeneous dispersion;

[0090] S4. Pour the homogeneous dispersion into a 300 ml rotating bottle, adjust the temperature of the heating oil bath to 50°C, adjust the rotation speed to 280 rpm, start the vacuum pump, adjust the pressure in the rotating bottle to 65 kPa, and introduce cooling water. After 30 minutes, a phosphorus-carbon composite negative electrode material coated with a conductive polymer film is obtained.

[0091] 2. Preparation of carbon aerogel-lithium manganese iron phosphate composite positive electrode material:

[0092] (1) 0.04 mol of ferrous nitrate, 0.06 mol of manganese nitrate, 0.05 mol of lithium carbonate, 0.1 mol of ammonium dihydrogen phosphate and deionized water are mixed to prepare solution A, so that the solid content is 40%; 0.2 mol of resorcinol (R), 0.4 mol of formaldehyde (F), 2 mmol of sodium carbonate (C) and 18 mol of deionized water (W) are uniformly mixed to form solution B; solution A is slowly added to solution B, stirred at room temperature for 4 hours to form solution C, and solution C is slowly injected into a cylindrical mold and allowed to stand at room temperature for 24 hours to form a sol;

[0093] (2) heating the sol at 50°C in a water bath for 24 hours, and then heating the sol to 75°C for further aging for 24 hours after the sol gels to obtain a dark red hydrogel; soaking the hydrogel sample in an ethanol solvent for 5 days, replacing the ethanol every 8 hours; placing the hydrogel after solvent replacement in an autoclave, sealing it, and heating it to a set temperature of 50°C at a heating rate of 1°C / min, with a set pressure of 15MPa. After keeping the temperature for 2 hours, slowly releasing the supercritical fluid to obtain an organic aerogel-lithium manganese iron phosphate precursor mixture;

[0094] (3) The organic aerogel-lithium iron manganese phosphate precursor mixture is carbonized in an argon atmosphere, heated to 800°C at a rate of 2°C / min, kept at this temperature for 2 hours, and then cooled in the furnace to obtain a carbon aerogel-lithium iron manganese phosphate composite positive electrode material.

[0095] 3. Preparation of lithium-ion hybrid supercapacitors with matched positive and negative electrodes

[0096] Step 1, take 8g of the above-mentioned carbon aerogel-lithium manganese iron phosphate composite positive electrode material, 1g of carbon black, 1g of polyvinylidene fluoride and N-methylpyrrolidone, stir and dissolve to obtain a positive electrode slurry (solid content 60%), and then coat it on a copper foil to obtain a positive electrode sheet;

[0097] Step 2, taking 7g of phosphorus-carbon composite negative electrode material, 1g of carbon black, 2g of polyvinylidene fluoride and N-methylpyrrolidone, stirring and dissolving them to obtain a negative electrode slurry (solid content 40%), and then coating it on a copper foil sheet to obtain a negative electrode sheet;

[0098] Step 3: In the presence of an electrolyte, the metal lithium foil is directly contacted with the negative electrode for 0.5 h, and then the negative electrode, the positive electrode and the electrolyte are assembled to obtain the lithium-ion hybrid supercapacitor; the electrolyte is 1M LiPF6 dissolved in EC / DEC (volume ratio 1:1) solution.

[0099] Example 4

[0100] 1. Preparation of phosphorus-carbon composite negative electrode materials:

[0101] S1. Disperse and dissolve 16 g of polypyrrole and 1 g of fullerene in 68 g of N-methylpyrrolidone, and stir magnetically for 12 h to obtain a polymer solution with a mass fraction of 20%;

[0102] S2, mixing black phosphorus quantum dots, graphite, carbon nanotubes and melamine and then ball milling to obtain an interface-modified phosphorus-carbon composite material, wherein the phosphorus-carbon composite material contains 50wt% of black phosphorus, 40wt% of graphite, 7wt% of carbon nanotubes and 3wt% of urea;

[0103] S3, taking 10g of the interface-modified phosphorus-carbon composite material and dispersing it in the polymer solution, ultrasonicating it for 5min, and magnetically stirring it for 6h to achieve uniform dispersion, and obtaining a 100g / L homogeneous dispersion;

[0104] S4. Pour the homogeneous dispersion into a 300 ml rotating bottle, adjust the temperature of the heating oil bath to 50°C, adjust the rotation speed to 280 rpm, start the vacuum pump, adjust the pressure in the rotating bottle to 65 kPa, and introduce cooling water. After 30 minutes, a phosphorus-carbon composite negative electrode material coated with a conductive polymer film is obtained.

[0105] 2. Preparation of carbon aerogel-lithium manganese iron phosphate composite positive electrode material:

[0106] (1) 0.08 mol of ferrous nitrate, 0.12 mol of manganese nitrate, 0.1 mol of lithium carbonate, 0.2 mol of ammonium dihydrogen phosphate and deionized water are mixed to prepare solution A, so that the solid content is 40%; 0.2 mol of resorcinol (R), 0.4 mol of formaldehyde (F), 2 mmol of sodium carbonate (C) and 18 mol of deionized water (W) are uniformly mixed to form solution B; solution A is slowly added to solution B, stirred at room temperature for 4 hours to form solution C, and solution C is slowly injected into a cylindrical mold and allowed to stand at room temperature for 24 hours to form a sol;

[0107] (2) heating the sol at 50°C in a water bath for 24 hours, and then heating the sol to 75°C for further aging for 24 hours after the sol gels to obtain a dark red hydrogel; soaking the hydrogel sample in an ethanol solvent for 5 days, replacing the ethanol every 8 hours; placing the hydrogel after solvent replacement in an autoclave, sealing it, and heating it to a set temperature of 50°C at a heating rate of 1°C / min, with a set pressure of 15MPa. After keeping the temperature for 2 hours, slowly releasing the supercritical fluid to obtain an organic aerogel-lithium manganese iron phosphate precursor mixture;

[0108] (3) The organic aerogel-lithium iron manganese phosphate precursor mixture is carbonized in an argon atmosphere, heated to 900°C at a rate of 2°C / min, kept at this temperature for 2 hours, and then cooled in the furnace to obtain a carbon aerogel-lithium iron manganese phosphate composite positive electrode material.

[0109] 3. Preparation of lithium-ion hybrid supercapacitors with matched positive and negative electrodes

[0110] Step 1, take 8g of the above-mentioned carbon aerogel-lithium manganese iron phosphate composite positive electrode material, 1g of carbon black, 1g of polyvinylidene fluoride and N-methylpyrrolidone, stir and dissolve to obtain a positive electrode slurry (solid content 50%), and then coat it on a copper foil to obtain a positive electrode sheet;

[0111] Step 2, taking 8g of phosphorus-carbon composite negative electrode material, 1g of carbon black, 2g of polyvinylidene fluoride and N-methylpyrrolidone, stirring and dissolving them to obtain a negative electrode slurry (solid content 50%), and then coating it on a copper foil sheet to obtain a negative electrode sheet;

[0112] Step 3: In the presence of an electrolyte, the metal lithium foil is directly contacted with the negative electrode for 0.5 h, and then the negative electrode, the positive electrode and the electrolyte are assembled to obtain the lithium-ion hybrid supercapacitor; the electrolyte is 1M LiPF6 dissolved in EC / DEC (volume ratio 1:1) solution.

[0113] Comparative Example 1

[0114] 1. Preparation of negative electrode materials:

[0115] The phosphorus-carbon composite negative electrode material was prepared by the same method as in Example 3.

[0116] 2. Preparation of positive electrode materials:

[0117] (1) 0.2 mol of resorcinol (R), 0.4 mol of formaldehyde (F), 2 mmol of sodium carbonate (C) and 18 mol of deionized water (W) were mixed uniformly to form a solution, the solution was slowly injected into a cylindrical mold, and allowed to stand at room temperature for 24 h to form a sol;

[0118] (2) The sol was heated in a water bath at 50°C for 24 hours, and after the sol was gelled, the temperature was raised to 75°C and the aging was continued for 24 hours to obtain a dark red hydrogel; the hydrogel sample was immersed in an ethanol solvent for 5 days, and the ethanol was replaced every 8 hours; the hydrogel after solvent replacement was placed in an autoclave, sealed and heated to a set temperature of 50°C at a heating rate of 1°C / min, and a set pressure of 15MPa. After keeping the temperature for 2 hours, the supercritical fluid was slowly released to obtain an organic aerogel material;

[0119] (3) The organic aerogel material is carbonized in an argon atmosphere, heated to 800°C at a rate of 2°C / min, kept at this temperature for 2 hours, and then cooled in the furnace to obtain a carbon aerogel positive electrode material.

[0120] 3. Preparation of lithium-ion hybrid supercapacitors

[0121] The carbon aerogel-lithium iron manganese phosphate composite positive electrode material in step 1 of Example 3 is replaced with the above-mentioned carbon aerogel positive electrode material; other technical features are the same as those in Example 3.

[0122] Comparative Example 2

[0123] 1. Preparation of positive electrode materials:

[0124] The carbon aerogel-lithium manganese iron phosphate composite positive electrode material was prepared by the same method as in Example 3.

[0125] 2. Preparation of lithium-ion hybrid supercapacitors

[0126] The phosphorus-carbon composite negative electrode material described in step 2 of Example 3 is replaced with a commercial graphite negative electrode material (manufacturer: B&T, model AGP-2L-P), and other technical features are the same as those of Example 3.

[0127] Test Results

[0128]

[0129]

[0130] It can be seen from the above test results that the lithium ion hybrid supercapacitor prepared by the method of the present invention has a high matching between the positive and negative electrodes in terms of kinetic process and specific capacity balance due to the use of high-capacity carbon aerogel-lithium iron manganese phosphate composite positive electrode material and high-rate, long cycle life phosphorus-carbon composite negative electrode material. The final lithium ion hybrid supercapacitor exhibits ultra-high energy density and power density as well as excellent cycle performance;

[0131] Since Comparative Example 1 uses a traditional capacitive carbon aerogel positive electrode material, compared with the capacitor-battery positive electrode hybrid mechanism, the discharge capacity is lower, resulting in poor matching with the battery-type negative electrode material, so that the energy density of the lithium ion hybrid supercapacitor prepared based on the negative electrode material is low at different power densities; Comparative Example 2 uses an embedded graphite negative electrode material with low capacity and poor rate performance, resulting in poor kinetic matching with the fast-charging positive electrode material, so that the lithium ion hybrid supercapacitor prepared based on the negative electrode material has a low energy density (especially at high power density) and poor cycle stability.

Claims

1. A method for preparing a lithium-ion hybrid supercapacitor with matched positive and negative electrodes, characterized in that: The following steps are involved: Step 1: taking a carbon aerogel-lithium manganese iron phosphate composite positive electrode material, a conductive agent, a binder and a solvent, stirring and dissolving them to obtain a positive electrode slurry, and then coating the mixture on a current collector sheet to obtain a positive electrode sheet; Step 2: taking a phosphorus-carbon composite negative electrode material, a conductive agent, a binder and a solvent, stirring and dissolving them to obtain a negative electrode slurry, and then coating the slurry on a current collector to obtain a negative electrode sheet; Step 3, pre-lithiating the negative electrode sheet, and then assembling the negative electrode sheet, the positive electrode sheet and the electrolyte to obtain the lithium ion hybrid supercapacitor; The method for preparing the phosphorus-carbon composite negative electrode material in step 2 comprises: S1, dispersing and dissolving the polymer and the conductive agent in a solvent to obtain a polymer solution; S2, mixing black phosphorus, graphite, carbon nanotubes and a small molecule modifier and then ball milling to obtain an interface-modified phosphorus-carbon composite material; S3, dispersing the interface-modified phosphorus-carbon composite material in a polymer solution to obtain a homogeneous dispersion; S4. Rotary evaporate the homogeneous dispersion to obtain a phosphorus-carbon composite negative electrode material coated with a conductive polymer film.

2. The method for preparing a lithium-ion hybrid supercapacitor with matched positive and negative electrodes according to claim 1, characterized in that: The method for preparing the carbon aerogel-lithium manganese iron phosphate composite positive electrode material in step 1 comprises: Step (1), mixing an iron source, a manganese source, a lithium source, a phosphorus source and deionized water to prepare a solution A, uniformly mixing resorcinol, formaldehyde, sodium carbonate and deionized water to form a solution B, slowly adding solution A to solution B with stirring to form a solution C, and allowing solution C to stand at room temperature to form a sol; Step (2), heating the sol to gel and age to obtain a hydrogel, and performing solvent replacement and supercritical drying on the hydrogel to obtain an organic aerogel-lithium manganese iron phosphate precursor mixture; Step (3), carbonizing the organic aerogel-lithium iron manganese phosphate precursor mixture under an inert atmosphere to obtain a carbon aerogel-lithium iron manganese phosphate composite positive electrode material.

3. The method for preparing a lithium-ion hybrid supercapacitor with matched positive and negative electrodes as claimed in claim 2, characterized in that: The manganese source in step (1) is a soluble manganese source selected from one of manganese sulfate, manganese nitrate, manganese acetate and manganese chloride; the phosphorus source is selected from one of phosphoric acid, diammonium phosphate, diammonium hydrogen phosphate and ammonium phosphate; and the lithium source is one of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate and lithium nitrate.

4. The method for preparing a lithium-ion hybrid supercapacitor with matched positive and negative electrodes according to claim 2, characterized in that: The molar ratio of the iron source, manganese source, lithium source and phosphorus source in the solution A in step (1) is 0.1-0.6:0.4-0.9:1:1-1.05 based on Fe, Mn, Li and PO4 respectively, and the solid content in the solution A is 40-60%.

5. The method for preparing a lithium-ion hybrid supercapacitor with matched positive and negative electrodes according to claim 2, characterized in that: In step (1), the molar ratio of resorcinol to formaldehyde in solution B is 1:2, the molar ratio of resorcinol to sodium carbonate is 100-1500:1, and the molar ratio of deionized water to resorcinol is 4-90:

1.

6. The method for preparing a lithium-ion hybrid supercapacitor with matched positive and negative electrodes according to claim 2, characterized in that: In step (1), the molar ratio of the Li element in solution A to the resorcinol in solution B is 1:1-4.

7. The method for preparing a lithium-ion hybrid supercapacitor with matched positive and negative electrodes according to claim 1, characterized in that: The mass ratio of the carbon aerogel-lithium manganese iron phosphate composite positive electrode material in step 1 or the phosphorus-carbon composite negative electrode material in step 2 to the conductive agent and the binder is 7-8:1:1-2, and the solid content of the positive electrode slurry and the negative electrode slurry is 40-60wt%.

8. The method for preparing a lithium-ion hybrid supercapacitor with matched positive and negative electrodes according to claim 1, characterized in that: The black phosphorus in step S2 is at least one of black phosphorus nanosheets and black phosphorus quantum dots.

9. A lithium ion hybrid supercapacitor prepared by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Black phosphorus-based composite negative electrode material, preparation method thereof and application of black phosphorus-based composite negative electrode material in metal secondary battery

    CN112018363A

  • Carbon aerogel network lithium manganese ferric phosphate battery electrode material and preparation method

    CN106887586A

  • Black phosphorene / MXene composite membrane electrode with piezoelectric property as well as preparation method and application of black phosphorene / MXene composite membrane electrode

    CN115207288A

  • Electrolyte, electrochemical device and electronic device

    CN116487694A

  • Phosphorus-carbon composite negative electrode material and preparation method and application thereof

    CN116799180A